Development of Accounting Media to Help Financial Literacy for SMEs in Surabaya - Yulius Hari; Melvie Paramitha; Darmanto; Indra Budi Trisno (JOINCS (Journal of Informatics, Network, and Computer Science), 2022)
Improvements in information technology and trade aspects during the COVID-19 pandemic provided a tremendous increase in financial inclusion, but unfortunately this was not matched by financial literacy, so that many MSMEs were disadvantaged by this. This activity aims to assist MSMEs in developing accounting media for MSMEs, so that they obtain real conditions related to more accurate bookkeeping. Data was collected by means of interviews and discussions. The results of discussions and observations with partners stated that a simple bookkeeping media was needed to help partners. Then from the results of this activity, they contribute in the form of simple accounting reporting media that help them manage finances better and provide reports that convey financial conditions quickly.